AI-GENERATED POLITICAL IMAGERY AND PUBLIC PERCEPTION IN RURAL KENYA: THE CASE OF THE "KASONGO" MEMES OF PRESIDENT WILLIAM RUTO - JAMES MBURU (Kabarak Journal of Research & Innovation, 2026)
The current study examines the impact that an AI-generated political picture, one of which was called Kasongo featuring President William Ruto, had on the perception of the rural Kenyan population. The research employed a qualitative and desk-based research approach, which entailed an analysis of over 120 memes and 2,500 social media messages on these social media platforms, such as WhatsApp and Facebook. The Media Dependency and Post-Truth theories put the work into context and show that synthetic media is a powerful tool to influence the political reputation of the masses and mobilize them in low-media-literacy conditions. These findings indicate that the audiences within the rural setting are unique in their responses to the impacts of the AI-powered disinformation due to the lack of infrastructure, the predisposition to rely on images, and the digital illiteracy. The memes cause the transformation in the long-term populist faith, which usurps the policy-based judgment by the popularity mediated by symbols. The article concludes that the institutional trust in AI-generated political imagery is being eroded and the political culture is being transformed, all of which demand urgent measures in the sphere of media literacy, responsibility of platforms, and civic engagement in rural areas.